Mechanism-based selection of stabilization strategy for amorphous formulations: Insights into crystallization pathways - Edueng, Khadijah; Mahlin, Denny; Larsson, Per Olof; Bergström, Christel A.S. (Elsevier B.V., 2017)
We developed a step-by-step experimental protocol using differential scanning calorimetry (DSC), dynamic vapour sorption (DVS), polarized light microscopy (PLM) and a small-scale dissolution apparatus (μDISS Profiler) to investigate the mechanism (solid-to-solid or solution-mediated) by which crystallization of amorphous drugs occurs upon dissolution. This protocol then guided how to stabilize the amorphous formulation. Indapamide, metolazone, glibenclamide and glipizide were selected as model drugs and HPMC (Pharmacoat 606) and PVP (K30) as stabilizing polymers. Spray-dried amorphous indapamide, metolazone and glibenclamide crystallized via solution-mediated nucleation while glipizide suffered from solid-to-solid crystallization. The addition of 0.001%–0.01% (w/v) HPMC into the dissolution medium successfully prevented the crystallization of supersaturated solutions of indapamide and metolazone whereas it only reduced the crystallization rate for glibenclamide. Amorphous solid dispersion (ASD) formulation of glipizide and PVP K30, at a ratio of 50:50% (w/w) reduced but did not completely eliminate the solid-to-solid crystallization of glipizide even though the overall dissolution rate was enhanced both in the absence and presence of HPMC. Raman spectroscopy indicated the formation of a glipizide polymorph in the dissolution medium with higher solubility than the stable polymorph. As a complementary technique, molecular dynamics (MD) simulations of indapamide and glibenclamide with HPMC was performed. It was revealed that hydrogen bonding patterns of the two drugs with HPMC differed significantly, suggesting that hydrogen bonding may play a role in the greater stabilizing effect on supersaturation of indapamide, compared to glibenclamide